Log price study in Peninsular Malaysia - Wan Zamani, Wan Abdul Rahman (2018)
The study of domestic log price and analysis is important for the wood-based industries. The objective of this study is to analyze the trend of nominal and real domestic log prices in Peninsular Malaysia. Specifically, the study is to determine the average monthly and annual growth rate, the significant difference of mean domestic log prices between species, month and year, and the correlation of domestic log prices between species. Nine species were selected in this study namely Red Balau, Balau, Mixed heavy Hardwood, Kempas, Kapur, Keruing, Red Meranti, Dark Red Meranti and Sepetir. This study covers the period from 2005 to 2016 using monthly log prices data collected from MASKAYU, an official bulletin of the Malaysian Timber Industry Board (MTIB). The results of the study show that nominal and real domestic log prices were on slow growth at the first 60 month and upward trend after this period. The estimated average growth rate of real domestic log prices, range from 0.5% to 0.8% per month and 6.0% to 9.6% per year. There is a significant difference of mean domestic log prices between species and year. The correlation analysis of domestic log prices indicates a positive correlation between the nine species. Further studies are needed to examine the relationship between domestic sawn timber production and mill estimated capacity.